Carbon‐Coated Supraballs of Randomly Packed LiFePO4 Nanoplates for High Rate and Stable Cycling of Li‐Ion Batteries. (30th May 2019) - Patil, Virendra; Oh, Woong; Yoo, Jong Won; Pu, Lyongsun; Park, Jong Hyeok; Yoon, Won‐Sub; Yi, Gi‐Ra
Abstract: One of the key strategies used to obtain high‐rate Li‐ion battery is the reduction of the Li‐ion path length inside the active materials and the enhancement of the ionic diffusion outside the active materials. It is demonstrated that electrochemical performance can be improved significantly at high C‐rates using carbon‐coated spherical aggregates or "supraballs" of randomly packed olivine LiFePO4 (LFP) nanoplates as cathode active materials. 258 nm LFP nanoplates with 30 nm thickness are synthesized through a high‐temperature solvothermal method, in which short lithium‐ion channels are formed perpendicular to the top or bottom planes. These thin nanoplates are formed into carbon‐coated "supraballs" through a spray‐drying and thermal annealing process, in which nanoplates are not stacked but randomly packed due to relatively fast drying. Internal and external nanoplate ion diffusion is therefore enhanced simultaneously due to the optimal molecular crystalline structure and interparticle pore structures of the nanoplates. Indeed, the initial capacity of the carbon‐coated supraballs is 162 mAh g −1 (173.34 mAh cm −3 ) at 0.1 C and more than 80% is retained (≈130.91 mAh g −1 ) at 50 C. Furthermore, they offer durable cycling stability (>500 cycles) at 1 C without compromising their capacity. Abstract : Carbon‐coated supraballs of olivine LiFePO4 nanoplates are developed as a cathode active material for the enhancement of Li‐ion battery performance at a high C‐rate. Thanks their microporous carbon coating and the short diffusion lengths of the LiFePO4 nanoplates and mesopores, they show 130.91 mAh g −1 of capacity at 50 C and stability over 500 cycles at 1 C.